Promoting Gender Equality in Teacher Helps to Learn and Too Young to Marry - Cutrey Febiola Adfias (Fakultas Ilmu Budaya, 2025)
This research analyzes the representation of gender equality in two digital storybooks, Teacher Helps to Learn and Too Young to Marry, published by UNICEF and featured in the Let's Read application. Using a qualitative method, this study applies Stuart Hall’s theory of representation specifically the semiotic approach by Roland Barthes and the discursive approach by Michel Foucault to explore how gender equality is constructed and communicated both visually and textually. The study aims to uncover how these stories promote gender equality and challenge gender stereotypes through the portrayal of characters, settings, and narratives. It highlights how female characters like Meena play active roles in pursuing education, resisting early marriage, and advocating for equal rights. In addition, the role of educators and family members reflects the potential for societal change through inclusive education and supportive environments. The findings indicate that Teacher Helps to Learn portrays gender equality by showing inclusive classroom settings where girls and boys learn equally under the guidance of a female teacher. Too Young to Marry emphasizes the right of girls to education and autonomy, criticizing the practice of early marriage. Both stories reflect UNICEF’s critical ideological stance in promoting children’s rights and gender equity. Ultimately, this research demonstrates that children's digital literature can function as a powerful medium to introduce values of equality and challenge patriarchal norms from an early age. These narratives not only reflect gender issues but also encourage young readers to develop critical awareness about equal opportunities for all genders.
Reuploud file repositori 10 maret 2026_Firli
Keywords: Gender; Gender Equality; Theory of Representation; Storybooks